Tails From Captive Classes: Interspecies Civic Action at the Contemporary Zoo - Schutten, Madrone Kalil; Shaffer, Emily (Frontiers in Communication, 2019)
In this case study we rearticulate the contemporary zoo to recognize the agency of captive classes. Contemporary zoos catalog the consequences of humans’ ecological choices. We reject the dominant ideologies used to justify captivity (e.g., human safety, rescue, and conservation), in favor of framing zoo’d animals as refugees forced into captivity due to human development and climate change. Through the permeability of zoo exhibit boundaries we analyze resistance from captive, free-living animals, and elemental nature (e.g. water), arguing for a strategic anthropomorphism that privileges intuition as a form of civic action that includes all entities. Moreover, we urge a shift toward a re-imagined model that implicates humans in the plight of the animals kept within zoo walls. This essay provides suggestions for an alternative zoo experience that responds to the resistive communication of more-than-humans.